Synthesis And Characterization Of Some Azobenzene Compounds And Their Derivatives Exhibiting Liquid Crystalline Properties - Ong , Chin Hin (2010)
The first series of compounds categorized as conjugated haloazobenzene typically 2,2’-(4-hydroxyl-1,3-phenylene)bis(1-(4-chlorophenyl)diazene) [ClC6H4N=NC6H3OHN=NC6H4Cl] were synthesized by coupling reaction under controlled temperature and concentration. This particular process has led to the attack of benzenediazonium upon both ortho and para positions of phenol as evident by spectroscopic and X-ray structural analyses. The subsequent reactions between the earlier synthesized haloazobenzenes with various bromoalkanes in even-parity (CnH2n+1Br where n = 6, 8, 10, 12, 14 and 16) have resulted in the formation of new compounds with dual-azo groups [ClC6H4N=NC6H3OHN=NC6H4Cl]. As for second series, a total of seven compounds classified as 2,2’-(4-alkoxy-1,3-phenylene)bis(1-(substitutedphenyl) diazene) of which the substituents are bromo (Br), methoxy (OCH3) and ethyl (C2H5) have been synthesized and isolated. The inductive effect from these substituents residing along the conjugated system in these dual-azo compounds was studied. The thermal properties associated with the incorporation of various carbon chains (CnH2n+1) of even-parity n ranging from n = 6, 8, 10, 12 and 14 have also been studied using thermally-controlled polarizing optical microscope